Hubungan Asupan Vitamin C dan Vitamin B12 dengan Kejadian Suspek Anemia pada Remaja Putri di Kabupaten Sukoharjo - Hapsari, Agesti Ayu; Hidayati, Listyani (Health Information : Jurnal Penelitian, 2023)
Anemia is a global nutritional problem that could occur in adolescence girls. The global prevalence of anemia for women aged 15-49 years is 29%. Lack of vitamin B12 intake can interfere with the process of formation of red blood cells. Lack of vitamin C intake can reduce iron absorption. This study aimed to find out the relationship between vitamin C and vitamin B12 intake with the suspected cases of anemia in adolescent girls in Sukoharjo District. This study was an analytical observational study with a cross-sectional approach on 110 subjects from 3 junior high schools in Sukoharjo (SMPN 2 Sukoharjo, SMPN 5 Sukoharjo, and SMPN 7 Sukoharjo) who had met the inclusion criteria of the study. The sampling technique was carried out using multistage sampling. Data retrieval of vitamin C intake and vitamin B12 intake used semiquantitative FFQ and the data of the suspected cases of anemia used by the early detection questionnaire of anemia signs. Data were analyzed using the chi-square test. The results of this study showed that subjects with less vitamin C intake were 57,3%, with less vitamin B12 intake were 61,8%, and the suspected cases of anemia were 34,5%. Chi-square test analysis related to vitamin C intake obtained a p-value was 0,924 and related to vitamin B12 intake was 0,007. There was no correlation between vitamin C intake with suspected cases of anemia in adolescent girl and there was a correlation between vitamin B12 intake with suspected cases of anemia in adolescent girl.